Дослідження характеру зносу гільз кристалізатора при високошвидкісній розливці сталі відкритим струменем - Рябий , Дмитро Валерійович; Смірнов , Олексій Миколайович; Шарандін , Кирило Миколайович; Ухін , Володимир Євгенович (Physico-technological Institute of Metals and Alloys, 2024)
Sleeve crystallizers are typically used for casting square billets with a cross section of up to 220-250 mm, as well as for casting round billets. Sleeve crystallizers are made of solid copper pipes with a wall thickness of 5 to 20 mm. A part with a specified cross-sectional profile, called a liner, is obtained from the tube billet using various metal forming methods to form the inner working wall of the crystallizer. The liner is inserted into a steel body and fastened at the top with a flange. The lower part of the liner is fixed in the body with a seal that allows free thermal expansion without deformation of the walls. Increasing the casting speed intensifies the heat flow and increases the deformation of the liner profile. These conditions not only accelerate wear processes, but also reveal defects in liner manufacturing and coating that are not detectable at low casting speeds. At present, Ukrainian metallurgical enterprises have accumulated a large amount of experimental material on the operation of crystallizers of continuous casting machines. However, in most cases, these data, which are necessary to increase the durability of crystallizers and improve the quality of products obtained at the enterprise, are not analyzed and generalized. The paper considers the causes of premature decommissioning and destruction of crystallizer sleeves of high-speed continuous casting machines. In real industrial conditions, the casting of a “long” series of metal using parabolic crystallizers at increased billet drawing speeds was investigated. During the industrial research, data were obtained and analyzed to determine the type of crystallizer liner design that has the highest operational life.